A cross-sectional study on the maternal outcome of an emergency caesarean section at different time intervals in a tertiary hospital - Ismail, Hamizah; Mohd Roslan, Noor Azrinawati; Ganeshan, Muniswaran (2022)
Background When compared to vaginal delivery, caesarean section (CS) is more likely to result in adverse maternal outcomes (AMO), especially if performed in an emergency manner. The question is whether emergency CS (emCS) after office hours carries a higher risk of AMO. Objective To investigate the relationship between the time when emCS delivery was performed and AMO. Methods This cross-sectional study included 211 cases of low-risk mothers who delivered via emLSCS at Hospital Tunku Azizah Kuala Lumpur from 1st to 31st August 2022. Those delivered through elective and semi-emergency CS were excluded. All data were gathered from the daily OT census and the HIS. They were divided into three groups based on the time the patient arrived at the OT. Daytime hours are 0700-1601, evening hours are 1601H-0000H, and early morning hours are 0001H-0659H). Maternal outcomes such as PPH, viscous injury, sepsis within 48 hours postpartum, unplanned ICU admission, relaparotomy, and hysterectomy were recorded and analysed using SPSS. Results The prevalence of composite AMO among emCS obtained was 5.20 %, which is consistent with previously reported studies where emCS complication is known to be very low, particularly in low-risk mothers. PPH is the most common, accounting for 11 cases, followed by one case of ICU admission following a caesarean hysterectomy. There has been no reported case of viscus injury and sepsis within 48 hours of delivery. There was no statistically significant correlation between delivery via emCS after office hours and composite AMO. The adjusted OR for emCS in the evening and early morning was 1.12 (95 percent CI 0.25-5.04) and 0.75 (95 percent CI 0.14-3.96), respectively. Conclusion In this study, which focused on low-risk mothers, there is no significant correlation between adverse maternal outcomes and the time when an emergency caesarean section was performed.